48‐4: LTPO Technology Development for Enhanced Display Performance: Image Sticking Phenomena, Circuit Operation and Backplane Process Integration. Issue 1 (28th June 2022) - Cho, Daeyoun; Moon, Jiho; Kihm, T.-Y.; Choi, Y.-T.; Park, Jongwoo
Abstract : This paper details the low temperature poly‐crystalline silicon oxide (LTPO) thin‐film transistor (TFT) technology development primarily focused on image sticking (IS) and recovery behaviors, the backplane process optimization, which is painstaking multi‐faceted approach from TFT to panel to circuit, in order to ensure display performance and reliability. Palpable understanding on light induced IS and recovery, the dependency of bias layout design and backplane process integration are crucial.